The Intratextual Fundamentalism Scale: cross-cultural application, validity evidence, and relationship with religious orientation and the Big 5 factor markers - Paul Williamson, W.; Hood, Ralph W.; Ahmad, Aneeq; Sadiq, Mahmood; Hill, Peter C. (2010)
This paper introduces a new five-item cross-cultural fundamentalism scale based on the principle of intratextuality. Free of belief content and concerns with militancy, each of the five items taps into a different facet of intratextuality that collectively assess the attitudes that fundamentalists maintain toward their sacred text—namely, a persuasion that it is divine in origin, inerrant, privileged above all other texts, authoritative, and unchanging as the embodiment of timeless truth. In this article, we present three studies concerned with the Intratextual Fundamentalism Scale (IFS). Study 1 introduces the development, confirmatory factor analysis, and convergent validity of the IFS based on a sample of 119 Christians in the US as well as examines its relationship to religious orientation. Study 2 replicates the findings of the first study with a sample of 220 Muslims from Pakistan. Study 3 again confirms the structure of the IFS, addresses divergent validity, and investigates its relationship with religious orientation and Goldberg's Big 5 factor markers in a sample of 227 US Christians. Findings of all three studies suggest that the IFS is a psychometrically sound instrument that economically assesses religious fundamentalism without religious content bias or concern for aggression. Results also indicate that, only for Americans, fundamentalism, as measured by the IFS, is significantly related to intrinsic (r = 0.35; r = 0.51) and extrinsic-personal (r = 0.33; r = 0.23) religious orientations, but not extrinsic-social orientation.
Keywords: Big 5 factor markers; Intratextual Fundamentalism Scale; Religious Orientation; validity evidence